Identification of Potential Drug Interaction with Complementary and Alternative Medicines among Chronic Disease Outpatients - Nurul Maziyyah; Apri Nurdianto; Arsitania Kun Fajria (International Journal of Public Health Science (IJPHS), 2018)
Chronic diseases such as congestive heart failure (CHF) and chronic kidney disease (CKD) are related with multiple drug prescription which can lead to drug interaction. The high usage of complementary and alternative medicines (CAM) in Indonesians can also increase the risk for drug interaction. The objective of this study is to describe CAMs use and identify potential drug interaction with CAMs in CHF and CKD outpatients. The study is a cross sectional study. Data of prescribed drugs and CAMs consumed by the patients was collected by using medication reconciliation process. Data of routine CAMs and prescribed medicines were compared to identify potential drug interactions which were then classified based on their mechanism and significance. The result showed that 6,90 % of CHF patients and 25 % of CKD patients consumed CAMs. Potential drug interaction between the CAMs and the prescribed drugs was identified in 2.74% of patients consuming CAMs. Based on the mechanism, interaction was dominated by pharmacodynamics interaction (69.2%) while interaction significancy was various. It can be concluded that CAMs usage was more familiar in CKD patients compared to CHF patients. Potential drug interaction with CAMs was able to be identified through medication reconciliation process and should be taken into awareness by the healthcare team.